Molecular Chaperone Receptors - Murshid, Ayesha (Methods Mol Biol, 2018)
Extracellular heat shock proteins (HSP) play important roles in cell signaling and immunity. Many of these effects are mediated by surface receptors expressed on a wide range of cell types. We have investigated the nature of such proteins by cloning candidate receptors into cells (CHO-K1) with the rare property of being null for HSP binding. Using this approach we have discovered that Hsp70 binds avidly to a least two classes of receptor including: (1) c-type lectin receptors (CLR) and (2) scavenger receptors (SR). However the structural nature of the receptor-ligand interactions is not clear at this time. Hsp70 can bind to LOX-1 (a member of both the CLR and SR), with the c-type lectin binding domain (CTLD) as well as the SR family members SREC-I and FEEL-1/CLEVER-1/STABILIN-1, which by contrast have arrays of EGF-like repeats in their extracellular domains. In this chapter we will discuss: (1) methods for discovery of HSP receptors, (2) approaches to the study of individual receptors in cells that contain multiple such receptors and (3) methods for investigating HSP receptor function in vivo.